Consumer Credit Fundamentals - Finlay, S. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2005)
Despite the huge expansion in consumer credit in the last 25 years there are very few texts describing the operation of consumer credit markets. Consumer Credit Fundamentals is the first book to provide a broad cross-disciplinary introduction to the subject. It covers the history of credit, the types of consumer credit available, how credit is granted and managed, the legal framework within which commercial lenders must operate, as well as consumer and ethical issues. A complete, well-rounded and practical introduction to consumer credit.